Development of Maize-T. Aus-T. Aman cropping pattern against Maize-Fallow-T. Aman rice (Progressive Agriculture, 2018)
The field experiment was conducted at MLT site Pirganj, Rangpur and Hatibandha’ Lalmonirhat for two consecutive years 2015-16 and 2016-17 to introduce T. Aus in the fallow period and to study the comparative agronomic performance and economic return of two cropping sequences (viz. improved cropping pattern; Maize -T. Aus - T. Aman rice and existing cropping pattern; Maize-Fallow-T. Aman rice) for increasing cropping intensity, productivity and land use efficiency. The experiment was laid out in randomized complete block design with six dispersed replications. Two years mean data showed that the improved management practices for the pattern provided significantly higher yield in improved pattern. Higher rice equivalent yield (REY) of cropping system (mean value 17.34 t ha-1) was recorded with the improved pattern over existing pattern at MLT site Pirganj. REY increased 4.60 t ha-1 by inclusion of T. Aus with improved production technologies for the component crops. Similar results were also found in Hatibandha. The gross return of the improved pattern was BDT 346764 ha-1 which was more than 33.56% higher than farmers’ pattern of BDT 259640 ha-1 at MLT site Pirganj and in Hatibandha gross return of the improved pattern was BDT 342800 ha-1 which was more than 27.77% higher than farmers’ pattern of BDT 268300 ha-1. The gross margin was higher in improved cropping pattern in both locations than existing pattern due to addition of T. Aus.Progressive Agriculture 29 (2): 107-116, 2018